2017
DOI: 10.1051/0004-6361/201730736
|View full text |Cite
|
Sign up to set email alerts
|

The GTC exoplanet transit spectroscopy survey

Abstract: We report the first detection of sodium absorption in the atmosphere of the hot Jupiter WASP-52b. We observed one transit of WASP-52b with the low-resolution Optical System for Imaging and low-Intermediate-Resolution Integrated Spectroscopy (OSIRIS) at the 10.4 m Gran Telescopio Canarias (GTC). The resulting transmission spectrum, covering the wavelength range from 522 nm to 903 nm, is flat and featureless, except for the significant narrow absorption signature at the sodium doublet, which can be explained by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 44 publications
4
49
2
Order By: Relevance
“…4.3, respectively. Chen et al (2017) obtained an absorption depth of ∆F/F = 0.378 ± 0.068% in a 16 Å band at Na with GTC low-resolution transmission spectrum, where the Na doublet is unresolved. For comparison, we integrated the ESPRESSO transmission spectrum over a 16-Å passband centered at the Na doublet (A ≈ 0.62%), and convolved it with a Gaussian kernel.…”
Section: Binned Absorption Depthmentioning
confidence: 98%
“…4.3, respectively. Chen et al (2017) obtained an absorption depth of ∆F/F = 0.378 ± 0.068% in a 16 Å band at Na with GTC low-resolution transmission spectrum, where the Na doublet is unresolved. For comparison, we integrated the ESPRESSO transmission spectrum over a 16-Å passband centered at the Na doublet (A ≈ 0.62%), and convolved it with a Gaussian kernel.…”
Section: Binned Absorption Depthmentioning
confidence: 98%
“…Most recently, Louden et al (2017) used spectroscopy between 4000 and 8750 Å for two transit observations from the ACAM instrument mounted on the William Herschel Telescope (WHT). Chen et al (2017) observed one transit with the Gran Telescopio Canarias's (GTC) OSIRIS instrument in the 5220−9030 Å wavelength range. We show these transmission spectra compared to our STIS+Spitzer results in Figure 9.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
“…We acquired 135 out-of-transit R-band images over the 2014-2015, 2015-2016, and 2016-2017 observing seasons with Tennessee State University's 14-inch Celestron Automatic Imaging Telescope (AIT). These observations, however, do not include the epochs of the Spitzer and groundbased (Chen et al 2017;Louden et al 2017) transit observations. We therefore used 740 out-of-transit V -band images from Ohio State University's All-Sky Automated Survey for Supernovae 2 (ASAS-SN) program (Shappee et al 2014;Kochanek et al 2017) for more detailed activity monitoring coverage.…”
Section: Stellar Variability Monitoringmentioning
confidence: 99%
“…All the tested models present a synthetic transit model with a time dependency to reproduce a second-order color effect not corrected by the differential photometry, and a FWHM dependent polynomial to model the systematic effects produced by seeing variations. The FWHM correction was introduced because seeing variations affected the number of pixels in which the major part of the stellar flux is contained, and this pixel-dependent effect will act as a systematic correlated with FWHM (see Nortmann et al 2016;Chen et al 2017). With a slit 40 arcsec in width, the flux losses produced by not being able to measure the flux contained in the wings of the spectral profile are negligible.…”
Section: Model Selectionmentioning
confidence: 99%
“…The principle of transmission spectroscopy is to measure the change in the planetary radius at different wavelengths during a transit event, and to use this change to infer the presence of particular components of the exoplanet atmosphere. Because of their relatively big atmospheric scale heights, hot Jupiters are excellent targets for atmospheric detection from the ground and they are the main targets of our survey (e.g., Murgas et al 2014;Parviainen et al 2016;Pallé et al 2016;Nortmann et al 2016;Chen et al 2017).…”
Section: Introductionmentioning
confidence: 99%